PENGARUH LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP KEMAMPUAN PENGELOLAAN KEUANGAN PELAKU USAHA MIKRO ( STUDI KASUS PADA USAHA MIKRO KOTA PEKANBARU) - Putri Riantika; Haryetti Haryetti; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aimed to test and seek empirical evidence regarding financial literacy and financial inclusion whether it affects the financial management ability of micro-entrepreneurs in Pekanbaru City. The population of this research is micro business located in Pekanbaru City by determining a sample of 100 micro business units with five existing business clusters. The results of this study indicate that financial literacy has a effect and significant influence on the financial management ability of micro business actors and financial inclusion also has a effect and significant influence on the financial management ability of micro business actors.Keywords: financial literacy, financial inclusion, financial management ability of micro entrepreneurs, micro businesses.